The Effects of Mindfulness Meditation on Emotion Regulation, Cognition and Social Skills - Thomas M. Jones (European Scientific Journal, ESJ, 2018)
This review seeks to bridge the gap between the separate but interacting mechanisms of emotion regulation and cognition, as well as their potential relationship with mindfulness meditation tools. By way of mindfulness meditation, individuals can learn how to regulate their emotions in a way that aversive stimuli will be viewed objectively; thus, the person can be free of attachment from said negative feelings. Knowing this, there is a potential link between emotion regulation processes and cognitive mechanisms that allow such regulation to take place, including selective or focused attention and inhibition. The literature on this theory so far has been inconsistent, however more claims suggest that there is a relationship between the two. This review initially speaks to existing mindfulness research and its implications on emotion regulation and cognitive processes. We then discuss emotion and the underlying processes and potential benefits of emotion regulation practice, as they are related to mindfulness mechanisms. Cognition, and the relationship between emotional intelligence and social skills are also discussed. Finally, we put it all together by suggesting a proactive mindfulness technique, which proves to be beneficial for each area mentioned.